Multisystemic Inflammatory Syndrome and Thrombotic Microangiopathy as Complications of COVID-19 in a Child: A Case Report - Samira Shizuko Parreão Oi; Monique Pereira Rêgo Muniz; Igor Murad Faria; Natalino Salgado Filho; Dyego José Araújo de Brito; Joyce Santos Lages; Letícia Pádua Lauande; Thina Klicia Mendonça Oliveira; Kaile de Araújo Cunha; Precil Diego Miranda de Menezes Neves; Gyl Eanes Barros Silva (Frontiers Media S.A., 2021)
Clinical presentations of the novel coronavirus (SARS-CoV-2) infection are quite varied, ranging from asymptomatic conditions to potentially fatal disease. The kidney is one of the affected targets of coronavirus disease (COVID-19) complications, and renal dysfunction is a significant prognostic factor for mortality. This report describes a series of clinical complications in a previously healthy child who developed nephritic syndrome with a concomitant SARS-CoV-2 infection. These complications include acute kidney injury that progressed to chronicity, multisystemic inflammatory syndrome, Kawasaki-like syndrome, and thrombotic microangiopathy.